Implementasi Ekstrakurikuler Rohani Islam (ROHIS) Dalam Penguatan Karakter Keteladanan Peserta Didik - Raito, Raito; Khoerunnisa, Eneng Ulfa (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
Extracurricular activities have important role in the process of strengthening the exemplary character of students. students. Learners who have values that will show good behavior to Allah SWT, fellow human beings, themselves and also the environment. behavior to Allah SWT, fellow humans, themselves and also the surrounding environment. Surrounding environment. For the success of strengthening exemplary character, the coach of extracurricular activities is expected to be able to strengthen the value of exemplary character. extracurricular activities coaches are expected to be able to strengthen the value of exemplary. Islamic Religious Education recently has problems, including religious education being in the spotlight society. The number of deviant behaviors of students and adolescents in general that are not in accordance with religious norms latel which is not in accordance with religious norms lately has prompted various parties to question the effectiveness of the implementation of religious education in schools. question the effectiveness of the implementation of religious education in schools. Seeingthese problems, it is necessary to have several breakthroughs, one of which can be done through the cultivation of good character from an early age that is applied in schools.can be done through the cultivation of good character from an early age that is applied at school both through learning in class and in schools both through learning in class and other activities such as ROHIS extracurricular activities. The research was conducted using qualitative field methods, carried out at MAN 2 Garut which aims to find out (1) ROHIS extracurricular profile at MAN 2 Garut (2) Strengthening the exemplary character of students at MAN 2 Garut (3) Implementation of ROHIS extracurricular activities at MAN 2 Garut. The results showed that to strengthen the exemplary character of students, it is necessary to implement character education and provide examples, one of which is through ROHIS extracurricular activities with reinforcement steps and the methods of teaching, modeling, habituation and rewarding. Keywords: extracurricular, exemplary, islamic spirituality